OPTIMALISASI PENGGUNAAN MEDIA SOSIAL DALAM PENINGKATAN BRAND AWARENESS PRODUK UMKM SETUBABAKAN (SULUH: Jurnal Abdimas, 2025)
This Community Service (PKM) program aims to optimize the use of social media for MSMEs in Setu Babakan so they can adapt and utilize technological advances to develop their businesses through social media training. Therefore, MSMEs are required to be able to create creative ideas and new innovations that can attract consumers. The training was conducted using a hands-on workshop method with simulations and mini-coaching. The results of the activity showed that participants agreed that the training had been carried out well, and agreed that social media marketing has a very significant influence on product marketing because it can increase sales volume and also increase profits for Micro, Small, and Medium Enterprises (MSMEs).